Public employment and the double role of bureaucrats - Matz Dahlberg; Eva Mörk (Institute for Labour Market Policy Evaluation (IFAU), 2004)
Bureaucrats in the government sector have a double role since they are both suppliers and demanders of public employment; they are publicly employed (supply labor) and they have an important say in deciding the size of the municipal employment (demand labor). In this paper we present and estimate a theoretical model that focuses on this double role of bureaucrats. The predictions from the theoretical model are supported by our empirical results: The estimates based on data from Swedish municipalities 19902002, show that wages have smaller effects on the demand for bureaucrats than on the demand for other types of public employees. Actually wages have no significant effect on the number of bureaucrats the municipality employs.
Keywords: J45; 330; Public employment; bureaucrats